2012
DOI: 10.1152/ajprenal.00023.2012
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxemia alters tight junction gene and protein expression in the kidney

Abstract: Intact tight junctional (TJ) proteins are required for tubular ion transport and waste excretion. Disruption of TJs may contribute to a decreased glomerular filtration rate in acute kidney injury (AKI) via tubular backleak. The effect of LPS-mediated AKI on murine TJs has not been studied extensively. We hypothesized LPS endotoxin administration to mice would disrupt tubular TJ proteins including zonula occludens-1 (ZO-1), occludin, and claudins. ZO-1 and occludin immunofluorescence 24 h post-LPS revealed a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
38
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 60 publications
(79 reference statements)
6
38
2
Order By: Relevance
“…Our results are in line with studies in mouse sepsis models, which also show marked reductions in occludin and claudin 5 levels (36,37). Studies in septic mice have also shown decreased ZO-1 expression and disorganized patterning with greater fragmentation, similar to our findings in the zebrafish sepsis model (38). We also saw upregulation of claudin 2 expression, pore forming tight junction protein, known to be markedly upregulated in mouse polymicrobial sepsis models (37).…”
Section: Discussionsupporting
confidence: 91%
“…Our results are in line with studies in mouse sepsis models, which also show marked reductions in occludin and claudin 5 levels (36,37). Studies in septic mice have also shown decreased ZO-1 expression and disorganized patterning with greater fragmentation, similar to our findings in the zebrafish sepsis model (38). We also saw upregulation of claudin 2 expression, pore forming tight junction protein, known to be markedly upregulated in mouse polymicrobial sepsis models (37).…”
Section: Discussionsupporting
confidence: 91%
“…In mice and other animal models, LPS induces AKI, which is accompanied by a robust inflammatory response including leukocyte infiltration (Wang et al, 2009;Zahedi et al, 2010;Eadon et al, 2012). Proximal tubular cells are thought to play a role in the interstitial leukocyte infiltration in kidneys because of their anatomic proximity and ability to produce proinflammatory mediators and chemotactic cytokines (Danoff, 1998;Wan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…33,34 Another possibility is paracellular back-leak due to alterations in the actin cytoskeleton and the disruption of tight junctions. 35 This leakage may occur only at the electrolyte level (i.e., water or sodium ions), because paracellular leakage of larger molecules, such as FITC-inulin and Lucifer yellow, was not observed. Using conditional KO mice (e.g., renal tubulespecific TLR4 KO mice) in combination with yet undeveloped advanced imaging techniques that enable the visualization of paracellular (or intracellular) ion leakage may more directly clarify the (molecular) mechanism.…”
Section: Discussionmentioning
confidence: 99%